Design and 3D printing of compliant mechanisms - Pham, Minh Tuan (2019)
Compliant mechanism has been a popular solution for developing precision motion systems. The working principle of compliant mechanism is based on elastic deformation of flexure elements, capable of providing highly repeatable motions that conventional bearing-based counterparts fail to deliver. In positioning applications, compliant parallel mechanism (CPM) is preferred because its closed-form architecture has high payload allowance and can better reject external mechanical disturbances. However, the performance of CPMs is often constrained by the limitations of synthesis techniques and fabrication methods. At present, it is still a challenge to synthesize multiple degrees-of-freedom (DOF) CPMs with spatial motions, optimized stiffness and dynamic properties. In addition, using conventional machining methods to fabricate the structure of CPMs by sub-parts will incur assembly errors. To address the limitations, this research focuses on the development of a new synthesis method for multi-DOF CPMs and the investigation on the mechanical characteristics of CPMs that are monolithically fabricated by 3D printing technology.